Modeling Concepts in Medicine for Medical Language Understanding - Rassinoux, A.-M.; Miller, R. A.; Baud, R. H.; Scherrer, J.-R. (Methods of Information in Medicine, 1998)
Over the past two decades, the construction of models for medical concept representation and for understanding of the deep meaning of medical narrative texts have been challenging areas of medical informatics research. This review highlights how these two inter-related domains have evolved, emphasizing aspects of medical modeling as a tool for medical language understanding. A representation schema, which balances partially but accurately with complete but complex representations of domainspecific knowledge, must be developed to facilitate language understanding. Representative examples are drawn from two major independent efforts undertaken by the authors: the elaboration and the subsequent adjustment of the RECIT multilingual analyzer to include a robust medical concept model, and the recasting of a frame-based interlingua system, originally developed to map equivalent concepts between controlled clinical vocabularies, to invoke a similar concept model.
Keywords: Natural Language Processing; Controlled Clinical Vocabularies; Medical Modeling; Conceptual Representation